Herbicides for Weed Control in Eucalyptus Culture - Anna Osiecka; Patrick Minogue (EDIS)
Eucalyptus is a diverse genus with over 700 species, most of which are native to Australia. Numerous Eucalyptus species and hybrid clones have been introduced in temperate climates throughout the world and grown as ornamental trees as well as for fuel and fiber. There is renewed interest in planting this fast-growing tree in the southeastern United States for mulch, pulpwood, and bioenergy. However, several silvicultural challenges exist, and competing vegetation control is a significant one. This 7-page fact sheet was written by Anna Osiecka and Patrick Minogue and published by the UF Department of School of Forest Resources and Conservation, February 2013.